THE EXPRESSION OF METAPHORICAL NOMINATION IN CHILDREN'S GAME NAMES IN UZBEK, ENGLISH, AND RUSSIAN LANGUAGES - Matmusaeva Mukhayyo Azamovna (Western European Studies, 2024)
This article explores the metaphorical nomination of children's game names in three languages: Uzbek, English, and Russian. By examining how metaphor is used in naming games, the study highlights the cultural, cognitive, and linguistic dimensions of games that shape children's understanding of the world. The study analyzes how metaphorical elements in game names evoke certain imagery, values, or concepts and reflect cultural traditions. A comparison between the three languages reveals both universal themes and unique cultural differences in metaphorical expression
Keywords: Metaphorical nomination; children's games; Uzbek language